Suggested Procedures According To COSO Integrated Framework To Evaluate The Internal Control System In Iraqi Oil Companies - Abdulakareem, Nawar Ali; Mohammed, Safaa Ahmed (Journal of Economics and Administrative Sciences, 2021)
The research amid to measure the extent of the Suggested procedures of the internal control in accordance with the updated COSO framework in improving the procedures for internal control work in Iraqi oil companies. As the research problem was represented in suggesting procedures for internal control according to the updated COSO framework and finding out the relationship of correlation and influence between the suggested procedures and the internal control procedures that are done in the Iraqi oil companies. The research followed the quantitative approach to handling and analysing data by designing a Questionnaire to represent the research tool for collecting data. The study population was represented in the Iraqi oil companies, while the study sample was (Midland Oil Company, Oil Pipelines Company, Petroleum Products Distribution Company, Midland Refineries Company). The results were that the internal control in its five components affects the internal control system in oil companies strongly, meaning that the Suggested procedures and the internal control system, which are related to each other, and the oil companies’ implementation of the Suggested internal control procedures according to the COSO framework will change and improve the internal control system accordingly. It is expected that the results of the current research will affect improving the internal control procedures in the Iraqi oil companies and encouraging them to adopt one of the global frameworks for internal control. Lastly, the current research represents the first research interested in evaluating internal control procedures in Iraqi oil companies by relying on modern international frameworks as a basis for evaluation